2005
DOI: 10.1002/sim.2234
|View full text |Cite
|
Sign up to set email alerts
|

Individual growth curve models for assessing evidence‐based referral criteria in growth monitoring

Abstract: SUMMARYThe goal of this study is to assess whether a growth curve model approach will lead to a more precise detection of Turner sydnrome (TS) than conventional referral criteria for growth monitoring. The JenssBayley growth curve model was used to describe the process of growth over time. A new screening rule is deÿned on the parameters of this growth curve model, parental height and gestational age. The rule is applied to longitudinal growth data of a group of children with TS (n = 777) and a reference (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
(19 reference statements)
0
22
0
Order By: Relevance
“…Childhood, the most stable growth period during the prepubertal years, may be the 'easiest' period during which to identify children with abnormal growth patterns [9]. However, variations in maturation and thereby tempo of growth in individual children during this phase need to be taken into account.…”
Section: Requirements Of a New Growth Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood, the most stable growth period during the prepubertal years, may be the 'easiest' period during which to identify children with abnormal growth patterns [9]. However, variations in maturation and thereby tempo of growth in individual children during this phase need to be taken into account.…”
Section: Requirements Of a New Growth Modelmentioning
confidence: 99%
“…A second reason is to describe growth patterns during the different phases of growth in order to detect individuals growing abnormal, and to identify the negative influences that may impair growth, such as diseases and syndromes [9]. The detection of abnormal growth is usually the main goal when creating reference data for use in healthcare systems worldwide [2][3][4][5][10][11][12][13][14][15].…”
Section: Why Is Human Growth Pattern Of Interest?mentioning
confidence: 99%
“…In a study of Indian children, Johnson et al (2012b) found that the Berkey-Reed 1st order model fitted better to infant weight and height data compared to other models such as the Count and 2nd order polynomial (quadratic) models. Studies that have modelled weight or height beyond 2 years have used models such as the Jenss-Bayley, Kouchi, adapted Jenss-Bayley and quadratic models and none of these did a comparative study on the fitness of the different models (Black & Krishnakumar, 1999; Botton et al, 2008; Dwyer et al, 1983; Martin-Gonzalez et al, 2012; van Dommelen et al, 2005). Some studies have used the quadratic model mainly for its simplicity and not necessarily because the model fits well to the data (Ehrenkranz et al, 1999; Grimm et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ecological and environmental influences that vary those monotonic functions are likely to lead to poorer fitting models, depending on the amount of variation that is driven by biological processes and the amount driven by ecological and environmental influences. Despite this, several studies have shown that the models can fit equally well to weight measurements (Botton et al, 2008; Dwyer et al, 1983; Johnson et al, 2012a, b; Pagezy & Hauspie, 1985; Simondon et al, 1992; van Dommelen et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…The Jenss-Bayley non-linear mixed effects model (JB growth model) (Dommelen et al, 2005), which describes the growth of children from birth to eight years of age on the basis of four parameters, was fitted to individual weight and height curves. It was not possible to model BMI directly, because of the complex shape of its trajectory.…”
Section: Growth Modelingmentioning
confidence: 99%